2015
DOI: 10.1080/00223980.2015.1004298
|View full text |Cite
|
Sign up to set email alerts
|

Mindfulness and False-Memories: The Impact of Mindfulness Practice on the DRM Paradigm

Abstract: Mindfulness practice is the cultivation of awareness to the present moment and has been shown in recent years to have beneficial effects on cognition. However, to date, the data regarding the impact of mindfulness on memory--and specifically on memory distortions--is scarce and incomplete. The present study was aimed to examine whether mindfulness practice would have an effect on true and false memories. To this end, the effect of mindfulness meditation practice on memory performance was examined in two experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
58
6

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(68 citation statements)
references
References 31 publications
4
58
6
Order By: Relevance
“…However, this conclusion is contradicted by findings from studies on mindfulness-based interventions [42,35]. We propose that being nonjudgmental should not reduce one's discriminability, because an essential component of the practice of mindfulness is increased attentiveness to sensory and perceptual stimuli and experiences.…”
Section: High Trait Mindfulness Associates With Low False Memorymentioning
confidence: 63%
See 2 more Smart Citations
“…However, this conclusion is contradicted by findings from studies on mindfulness-based interventions [42,35]. We propose that being nonjudgmental should not reduce one's discriminability, because an essential component of the practice of mindfulness is increased attentiveness to sensory and perceptual stimuli and experiences.…”
Section: High Trait Mindfulness Associates With Low False Memorymentioning
confidence: 63%
“…Two recent studies have reported increased false memory in a DRM paradigm task after mindfulness training [42,35], whesreas others indicate otherwise [8,10,12,25].…”
Section: Mindfulness and True Memorymentioning
confidence: 99%
See 1 more Smart Citation
“…Loneliness has been argued to be intimately related to cognitive deficiencies, such as difficulty in attention disengagement [39] and heightened memory attunement toward social information [40]. Hence, mindfulness may reduce the cognitive effects of loneliness by increasing memory [26,41] and attention [42], or by reducing the role of emotions in the processes of perception and decision making [43].…”
Section: Discussionmentioning
confidence: 99%
“…The second study was conducted about a month later and was aimed to examine the impact of mindfulness practice on memory. Specifically, students participated in mindfulness workshops in which they acquired the basics of mindfulness meditation practice, and they were compared with control participants in various memory measures [26]. We combined data from both studies along with the students' mean grades at the end of the first semester (i.e.…”
mentioning
confidence: 99%